Dynamic balance in alpine skiers - Cresswell, T.; Mitchell, A.; Hewitt, N. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
There are more than 200 million alpine skiers worldwide (Hunter, 1999) but currently ski equipment does not protect the knee as it does the rest of the lower leg and there has been a dramatic rise in knee ligament and meniscus injuries associated with alpine skiing in recent years (Pecina, 2002). Pujol et al. (2007) stated that 45-60% of knee injuries during alpine skiing involve the ACL. Balance is an important component of performance in skiing (Laskowski, 1999) and Natri et al. (1999) found that many skiers sustaining an injury believed they were only temporarily off balance and capable of regaining control. The three most common mechanisms of injury to the knee in skiing are linked to a loss of dynamic balance (Rossi et al., 2003).